Toxicokinetics of silver nanoparticles in freshwater benthic invertebrates - Silva, Patrícia Maria Veríssimo de Pinho e (2022)
The nanotechnology industry has grown exponentially in the last decade, inevitably leading to the release of engineered nanomaterials (ENMs) into the environment. Sediments can be important environmental sinks for ENMs, potentially threatening benthic biota. For a sustainable nanotechnology a robust environmental risk assessment is required to ensure the preservation of the ecosystems while supporting innovation. In line with this, studies on the bioaccumulation and toxicokinetics of ENMs have been highly requested by regulatory parties. Aiming to contribute to this subject, the present thesis focuses on determining and understanding the toxicokinetics of different pristine silver nanoparticles (Ag NPs), silver sulfide nanoparticles (Ag2S NPs, used as model of an environmentally aged Ag NP form) and AgNO3 in freshwater benthic invertebrates. The ecologically relevant species Physa acuta, Chironomus riparius and Girardia tigrina were chosen as test organisms and exposed to the different NPs through different routes. In the first study, the snail P. acuta was exposed to 1) contaminated water (without sediment), 2) contaminated water with clean sediment, and 3) contaminated sediment. Results revealed fast uptake and depuration of Ag from Ag2S NPs by the snails in all experiments. Water exposure was the predominant Ag uptake route for P. acuta. It was also shown that bioavailability of Ag to the snails was greatly influenced by the Ag characteristics and by the exposure route. C. riparius larvae were exposed to the different Ag forms via water, sediment, or food. Results consistently revealed higher Ag uptake by the chironomid larvae upon exposure to Ag2S NPs, while larvae exposed to pristine Ag NPs and AgNO3 generally presented similar toxicokinetics. Uptake of Ag by the larvae was better explained by exposure to water than from the ingestion of sediment particles in both water and sediment exposure tests. Food exposure resulted only in Ag uptake in the Ag2S NP treatment. For the next study, P. acuta was first exposed to Ag-spiked water (Ag2S NP and AgNO3) and fed with (clean) microalgae, and subsequently provided as pre-exposed food to the planarians G. tigrina. Both species revealed higher Ag uptake from AgNO3 than from Ag2S NP treatment. Uptake of Ag by the snails was probably via a combination of water exposure and ingestion of microalgae. Planarians accumulated Ag from the food in both Ag2S NP and AgNO3 treatments, but no apparent risk for biomagnification was observed in the food chain P. acuta → G. tigrina. To the best of our knowledge this is the first study investigating the toxicokinetics of NPs in planarians. Finally, an indoor mesocosm experiment simulating a stream environment was conducted to evaluate the toxicokinetics, bioaccumulation and biomagnification potential of Ag2S NP. Furthermore, it was investigated whether single-species tests can predict Ag bioaccumulation in the mesocosm test. The species G. tigrina, P. acuta and C. riparius bioaccumulated Ag in both Ag2S NP and AgNO3 exposures, but showed higher internal Ag concentrations upon AgNO3 exposure. The uptake observed in the Ag2S NP treatment was probably in the particulate form, revealing bioavailability of this more environmentally persistent and relevant Ag nanoparticulate form in a more realistic exposure scenario. Single-species tests generally were not able to reliably predict Ag bioaccumulation in the more complex mesocosm system. Moreover, no risk for biomagnification was observed in Ag2S NP treatment under this environmentally realistic exposure scenario, however it seemed to occur in the food chain P. acuta → G. tigrina in the AgNO3 treatment. This was the first study investigating the toxicokinetics of Ag2S NPs in benthic invertebrates in a freshwater mesocosm experiment. This work provides important data for modelling the potential exposure and bioaccumulation of Ag from Ag NPs exposures, including Ag2S NPs, in freshwater benthic environments. The data generated in the present thesis may be useful for predictive models for nano regulation purposes, contributing to improving the environmental risk assessment of ENMs.